2015
DOI: 10.1007/s12031-015-0689-0
|View full text |Cite
|
Sign up to set email alerts
|

BDNF/TrkB Signaling as a Potential Novel Target in Pediatric Brain Tumors: Anticancer Activity of Selective TrkB Inhibition in Medulloblastoma Cells

Abstract: Medulloblastoma (MB) is the most common malignant pediatric brain tumor. Deregulation of brain-derived neurotrophic factor (BDNF)/tropomyosin-related kinase B (TrkB) signaling has been associated with increased proliferative capabilities, invasiveness, and chemoresistance in several types of cancer. However, the relevance of this pathway in MB remains unknown. Here, we show that the selective TrkB inhibitor N-[2-[[(hexahydro-2-oxo-1H-azepin-3-yl)amino]carbonyl]phenyl]-benzo[b]thiophene-2-carboxamide (ANA-12) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The involvement of NTs and TRKs in oncogenesis has been investigated in several types of tumors [32-40], and NT activation of TRK receptors has been shown to be involved in early-stage malignancy development, metastasis, and resistance to treatment [41-44]. In an IHC study of 15 cutaneous melanomas, 12 melanoma metastases, and 16 benign pigment cell lesion samples, Innominato et al [22] found that the expression of NGF, BDNF, NT-3, and their receptors (p75, TrkB, and TrkC) was more frequent in cutaneous melanoma and metastasis samples than in benign lesions or normal skin [22].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of NTs and TRKs in oncogenesis has been investigated in several types of tumors [32-40], and NT activation of TRK receptors has been shown to be involved in early-stage malignancy development, metastasis, and resistance to treatment [41-44]. In an IHC study of 15 cutaneous melanomas, 12 melanoma metastases, and 16 benign pigment cell lesion samples, Innominato et al [22] found that the expression of NGF, BDNF, NT-3, and their receptors (p75, TrkB, and TrkC) was more frequent in cutaneous melanoma and metastasis samples than in benign lesions or normal skin [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that p75NTR is expressed predominantly in the SHH subgroup [107], but the functional consequence of this remains to be determined. BDNF and TrkB signaling effects in medulloblastoma are even less clear, with one study reporting exposure to BDNF and reduced viability in human medulloblastoma cell lines [108]; but another study reporting a similar effect with TrkB inhibition [109]. The function of neurotrophin signaling in ependymomas is also an area that requires investigation.…”
Section: The Role Of Neurons In Ectodermal Tissuesmentioning
confidence: 99%
“…7 Another recent study has suggested that glioma growth may be regulated by TrkB expressed in exosomes. 8 We have recently provided evidence for a potential role of TrkB inhibition as a strategy to reduce cell proliferation and potentiate the effects of chemotherapy in medulloblastoma 9 and Ewing sarcoma. 10 In order to investigate the antitumor effects of pharmacological inhibition of TrkB-associated signaling, Ni et al used the compounds AZD1480, a janus kinase (JAK) inhibitor, and RXDX-101, which nonselectively inhibit different members of the Trk receptor family (TrkA, TrkB, and TrkC), C-ros oncogene 1 (ROS1), and the anaplastic lymphoma kinase (ALK).…”
Section: Targeting Tyrosine Receptor Kinase B In Gliomasmentioning
confidence: 99%